The Diagnostic Value of 3.0 T Magnetic Resonance Imaging Combined with Carbohydrate Antigen 125 and Human Epididymis Protein 4 in Epithelial Ovarian Cancer - Tie Cao; Dongqing Wang; Xiaoyu Chen; Lirong Zhang; Wanhong Chen (Clinical and Experimental Obstetrics & Gynecology)
Background: Epithelial ovarian cancer (EOC) is among the top 5 causes of cancer-associated death in women. We explored the diagnostic value of 3.0 T magnetic resonance imaging (MRI) combined with carbohydrate antigen 125 (CA125) and human epididymis protein 4 (HE4) on EOC. Methods: Among 380 ovarian space-occupying patients in this retrospective analysis, 344 were included, 59 were excluded, 25 had incomplete clinical data, and 260 were finally included as the subjects. Patients were classified into the EOC (110 patients with EOC) and N-EOC (150 patients without EOC) groups. The levels of interleukin-6 (IL-6), C-reactive protein (CRP), follicle stimulating hormone (FSH), luteinizing hormone (LH), anti-mullerian hormone (AMH), CA125, and HE4 were determined. The apparent diffusion coefficient (ADC) value and the clinical diagnostic value of MRI, CA125, HE4, and their combination were analyzed. Results: There were significant differences in tumor family history, gravidity, parity, IL-6, CRP, FSH, LH, AMH, and ADC value between EOC and N-EOC patients (all p < 0.05). EOC patients exhibited highly-expressed CA125 and HE4 (p < 0.01). CA125/HE4 expression was correlated with the clinicopathological features of EOC, while the ADC value was correlated with the EOC tumor diameter (all p < 0.05). MRI [area under the curve (AUC) = 0.77], CA125 (AUC = 0.85) and HE4 (AUC = 0.90) had certain diagnostic value for EOC (all p < 0.05). Conclusions: The prevalence of EOC in ovarian space-occupying patients with highly-expressed CA125 and HE4 is higher. MRI combined with CA125 and HE4 has high clinical diagnostic value for EOC.